Effect of photoperiod on endocrine profiles and vitellogenin expression in European eels Anguilla anguilla during artificially induced ovarian development - Parmeggiani, A.; Govoni, N.; Zannoni, A.; Di Biase, A.; Sirri, R.; Forni, M.; Mandelli, M.; Mordenti, O. (Theriogenology, 2015)
The aim of this work was to determine the effects of dark and light conditions on the E2, testosterone and thyroid hormones levels and on the gene expression levels (vitellogenin 1, vitellogenin 2, and estradiol receptor one) in European eels (Anguilla anguilla) during ovarian development induced by increasing doses of carp pituitary extracts (CPEs). The subjects were divided into 2 groups: 14-hour light:10-hour dark (Light Group) and 24-hour darkness (Dark Group). All the eels received intramuscular injections with CPE at a dosage of 10 mg/kg body weight (BW) once a week for the first 3 weeks, 20 mg/kg BW fourth-sixth week, 30 mg/kg BW seventh-ninth week, and 40 mg/kg up to the end of the experiment (13th week). Vitellogenin and estradiol receptor expression levels did not show significant differences between the two housing conditions whereas in both groups vitellogenin mRNA increased starting from first CPE injection. Testosterone and 17-beta estradiol plasma levels were significantly greater in the Dark Group compared with the Light Group starting from the ninth and the 13th week, respectively. These results suggest that darkness could be a useful variable for standardizing gonadal maturation in eels kept in captivity.